Pilot Study on the Role of Facial Acupuncture in Achieving Skin Hydration and Oil Equilibrium - J, Praveena, Gokulakrishnan; Narasimman, Prabu; Sankar, Geetanjali (Indian Journal of Integrative Medicine, 2025)
Healthy, youthful skin profoundly affects confidence and self-esteem. Maintaining a balance between oil and water content is vital for a radiant complexion. However, aging, lifestyle, and environmental factors can disrupt this balance, causing skin dullness and premature aging. Many seek natural, non-invasive interventions like cosmetic acupuncture, rooted in traditional Chinese medicine. Despite its popularity, robust scientific validation remains limited. This study investigates the effectiveness of cosmetic acupuncture in enhancing facial aesthetics. The study included ten women aged 20–35 from the International Institute of Yoga and Naturopathy Medical Sciences, Chengalpattu, randomly assigned to either a Facial Cosmetic Acupuncture (FCA) group (n=5) or a control group (n=5). The FCA group underwent 30-minute treatment sessions twice weekly, while the control group received no intervention. Skin hydration and oil levels were measured using a Facial Skin Analyzer at baseline, weekly during the intervention, and four weeks post-intervention. Subjective changes in appearance were evaluated using the Patient’s Aesthetic Improvement Scale (PAIS) and the Global Aesthetic Improvement Scale (GAIS). The FCA group demonstrated significant improvements in skin hydration and oil balance compared to the control group. Increased water content and decreased oil levels were observed, with treatment efficacy varying by age. Subjective assessments from PAIS and GAIS aligned with these findings, as participants reported moderate to substantial improvements in skin appearance. Mechanisms potentially underlying these effects include enhanced collagen synthesis, lymphatic drainage, and aquaporin-3 activation. Facial Cosmetic Acupuncture effectively improves skin hydration and oil balance, offering a non-invasive solution for skin health. This study highlights the need for further research on long-term effects and optimized treatment protocols. The findings underscore FCA’s potential as a valuable therapeutic option in promoting skin aesthetics and overall well-being.